2023
DOI: 10.1002/ijgo.14703
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of prenatal care practitioners regarding oral health in pregnancy—A systematic review

Abstract: Women undergo multiple stages in the course of their life, such as puberty, pregnancy, and menopause, and these can influence their oral health due to hormonal changes. 1 During pregnancy, there is an increase in the secretion of progesterone and estrogen, leading to periodontal hypervascularization, alterations in the production of collagen, and increased susceptibility to oral biofilm, which may exacerbate pre-existing gingivitis or periodontitis. 1,2 The relationship between periodontal diseases and adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(261 reference statements)
0
2
0
Order By: Relevance
“…Gynecologists and midwives, as reported by the participants, do not seem inclined to invest time and effort in their patients' oral health. In agreement with these ndings, a recent systematic review concluded that gynecologists, obstetricians, nurses, and general practitioners are aware of the importance of oral health during pregnancy but still fail to translate this knowledge into clinical practice [40]. A non-negligible percentage of women reported experiencing oral problems during pregnancy, in line with those reported in American and Canadian women samples [41,42].…”
Section: Discussionmentioning
confidence: 89%
“…Gynecologists and midwives, as reported by the participants, do not seem inclined to invest time and effort in their patients' oral health. In agreement with these ndings, a recent systematic review concluded that gynecologists, obstetricians, nurses, and general practitioners are aware of the importance of oral health during pregnancy but still fail to translate this knowledge into clinical practice [40]. A non-negligible percentage of women reported experiencing oral problems during pregnancy, in line with those reported in American and Canadian women samples [41,42].…”
Section: Discussionmentioning
confidence: 89%
“…Gynecologists and midwives, as reported by the participants, seem unwilling to invest time and effort in their patients’ oral health. In agreement with these findings, a recent systematic review concluded that gynecologists, obstetricians, nurses, and general practitioners are aware of the importance of oral health during pregnancy but still fail to translate this knowledge into clinical practice [ 41 ]. A non-negligible percentage of women reported experiencing oral problems during pregnancy, in line with those reported in American and Canadian women samples [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 92%